Prevalence and Genetic Characteristics of Staphylococcus aureus CC398 Isolates From Invasive Infections in Spanish Hospitals, Focusing on the Livestock-Independent CC398-MSSA Clade - Mama, Olouwafemi Mistourath; Aspiroz, Carmen; Ruiz-Ripa, Laura; Ceballos, Sara; Iñiguez-Barrio, Maria; Cercenado, Emilia; Azcona, José Manuel; López-Cerero, Lorena; Seral, Cristina; López-Calleja, Ana Isabel; Belles-Belles, Alba; Berdonces, Pilar; et al. (Frontiers in Microbiology, 2021)
Background Livestock-associated (LA)-CC398-MRSA is closely related to pigs, being unfrequently detected in human invasive infections. CC398-MSSA is emerging in human invasive infections in some countries, but genetic and epidemiological characteristics are still scarcely reported. Objectives To determine the prevalence of Staphylococcus aureus (SA) CC398, both MRSA and MSSA, among blood cultures SA isolates recovered in Spanish hospitals located in regions with different pig-farming densities (PD) and characterize the recovered isolates. Methods One thousand twenty-two SA isolates (761 MSSA, 261 MRSA) recovered from blood cultures during 6–12 months in 17 Spanish hospitals (2018–2019) were studied. CC398 lineage identification, detection of spa-types, and antibiotic resistance, virulence and human immune evasion cluster (IEC) genes were analyzed by PCR/sequencing. Results Forty-four CC398-MSSA isolates (4.3% of SA; 5.8% of MSSA) and 10 CC398-MRSA isolates (1% of SA; 3.8% of MRSA) were detected. Eleven spa-types were found among the CC398-MSSA isolates with t571 and t1451 the most frequent spa-types detected (75%). Most of CC398-MSSA isolates were Immune-Evasion-Cluster (IEC)-positive (88.6%), tetracycline-susceptible (95.5%) and erythromycin/clindamycin–inducible-resistant/erm(T)-positive (75%). No statistical significance was detected when the CC398-MSSA/MSSA rate was correlated to PD (pigs/km2) (p = 0.108). On the contrary, CC398-MRSA isolates were all IEC-negative, predominately spa-t011 (70%), and the CC398-MRSA/MRSA rate was significantly associated to PD (p < 0.005). Conclusion CC398-MSSA is an emerging clade in invasive infections in Spanish hospitals. CC398-MRSA (mostly t011) and CC398-MSSA (mostly t571 and t1451) show important differences, possibly suggesting divergent steps in host-adaptation evolutionary processes. While CC398-MRSA is livestock-associated (lacking IEC-system), CC398-MSSA seems to be mostly livestock-independent, carrying human-adaptation markers.